PEMBELAJARAN KUANTUM TERHADAP KEMAMPUAN MOTORIK HALUS ANAK CEREBRAL PALSY DI SDLB-D1 - ZAKARIA ELMI, AKHMAD (Jurnal Pendidikan Khusus, 2018)
ABSTRACT The less fine motor skills of cerebral palsy children led to their difficulties in doing their daily activities especially in school environment like writing and other activities that require fine motor skills. The purpose of this study to know whether there is influence of quantum learning on the fine motor skills of cerebral palsy children in SDLB-D1 YPAC Surabaya. This study aims to train and develop fine motor skills of cerebral palsy children using quantum learning by applying motor activity. This research used a quantitative approach with pre-experimental research by One Group Pre-test Post-test Design. The subject of this study were 6 students of class 1-3 in SDLB-D1 YPAC Surabaya. The data analysis revealed that the average score for the pre-test was 37,40 and the post-test was 60,73. Using the sign test, it was obtained that Zobserved= 2,05 was higher than crisis values =1,96, meaning that Ho was rejected and Ha was accepted. Thus, it showed that quantum learning fine motor skills of cerebral palsy children  at SDLB-D1 YPAC Surabaya. Keyword: Quantum Learning, Fine Motor Skills, Cerebral Palsy